1984
DOI: 10.1083/jcb.98.5.1696
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical studies on the localization of plasma and of cellular retinol-binding proteins and of transthyretin (prealbumin) in rat liver and kidney.

Abstract: The immunocytochemical localization of cellular retinol-binding protein (CRBP), of plasma retinol-binding protein (RBP), and of plasma transthyretin (TTR) was studied in rat liver and kidney. The studies employed normal rats, retinol-deficient rats, and rats fed excess retinol . Antisera were prepared in rabbits against purified rat CRBP, RBP, and TTR . The primary antibodies and goat anti-rabbit IgG were purified by immunosorbent affinity chromatography, using the respective pure antigen coupled to Sepharose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 42 publications
2
56
0
1
Order By: Relevance
“…In rats, vitamin A deficiency blocks the secretion of RBP from the liver, so that plasma RBP concentrations fall and liver RBP levels rise [1,7]. These observations are consistent with a much stronger intensity of staining for immunoreactive RBP in the liver of vitamin A deficient rats [9].…”
Section: Tissue Distribution Of Vitamin a And Rbpsupporting
confidence: 71%
See 1 more Smart Citation
“…In rats, vitamin A deficiency blocks the secretion of RBP from the liver, so that plasma RBP concentrations fall and liver RBP levels rise [1,7]. These observations are consistent with a much stronger intensity of staining for immunoreactive RBP in the liver of vitamin A deficient rats [9].…”
Section: Tissue Distribution Of Vitamin a And Rbpsupporting
confidence: 71%
“…Consequently, immunoreactive RBP could be detected in the proximal convoluted tubules as described in human and rat kidneys [8,9]. This result and the high vitamin A concentrations in the kidneys of raccoon dogs and silver foxes despite low vitamin A concentrations in the livers suggest a specific function of the canine kidney in contributing plasma retinol and retinyl esters in addition to the excretion of vitamin A with the urine [27].…”
Section: Tissue Distribution Of Vitamin a And Rbpmentioning
confidence: 96%
“…2a). CRBP-1 was expressed at a high level in HSC and slightly in hepatocytes as previously described (Kato et al, 1984); in the parenchyma, the distribution of CRBP-1-expressing HSC was homogeneous. In portal areas, the fibroblastic cells did not express CRBP-1 (Fig.…”
Section: Uchio Et Almentioning
confidence: 99%
“…Several studies have examined the expression of CRBP-1 in the different cell types of the liver Blomhoff et al, 1985;Kato et al, 1984). Hepatocytes and HSC contain large amounts of CRBP-1.…”
mentioning
confidence: 99%
“…Nagy et al (19) reported that very few lipid droplet containing stellate cells were found in the interstitial regions of kidney cortex regardless of whether animals were fed a vitamin Asufficient or excessive diet suggesting that in the vitamin Adeficient rats, little R, RE, and presumably DR and DRE were stored in renal stellate cell lipid droplets. Kato, Kato, and Goodman (53) reported that RBP traveled to the apical portions of the proximal convoluted tubular cells, and this represented RBP that had already undergone glomerular filtration and tubular reabsorption. This report of RBPʼs renal cellular location suggests that R may colocalize there.…”
Section: Discussionmentioning
confidence: 99%